Cutaneous wound healing through paradoxical MAPK activation by BRAF inhibitors - Helena Escuin-Ordinas (Nature Portfolio, 2016)
BRAF inhibitors often show skin-hyperproliferative side effects in melanoma patients. Here, the authors demonstrate that BRAF inhibitors can be used to enhance skin wound healing through the MAPK- ERK pathway activation that positively regulates the proliferation of keratinocytes.